Fibrilasi Atrial Selama Perawatan Infark Miokard Akut Merupakan Prediktor Stroke Jangka Panjang - Manoefris Kasim; Octavia Lilyasari; Yoga Yuniadi (Jurnal Kardiologi Indonesia, 2011)
Background. Atrial fibrillation (AF) is a common arrhythmia after acute myocardial infarction (AMI).Mortality in AMI patients with AF also been shown to be up to twice as high as for those without AF. Non hemorrhagic stroke occurs in 0.1% to 1.3%of patients with acute myocardial infarction who are treatedwith thrombolytic, with substantial associated mortality and morbidity. The aim of this study is toelaborate correlation between in hospital AF with long term stroke event inST-elevation myocardial infarction (STEMI) patients who treated with thrombolytic.Methods. Two hundred and thirty STEMI patients (27-72 yo) treated with thrombolytic agent were studied retrospectively. The study end point was Major Cardio-Cerebrovascular Event (MACCE) during 3 years follow up. Results. Eleven patients experience AF episode during STEMI hospitalization. During 3 years follow up 24 patients (10.4%) experienced MACCE which comprised of : cardiac death 4 (1.7%), fatal infarction 2 (0.9%), non fatal infarction 13 (5.7%) and stroke 5 (2.2%). Independent clinical variables were not significant as a predictor for the occurrence of future stroke event, except atrial fibrillation episode (HR 13.4; p<0.005) that was encountered during hospitalization in the setting of AMI.Conclusion. In-hospital AF in STEMI patients treated with thrombolytic agent is a predictor of long term stroke.